Analysis of Students' Scientific Literacy Abilities with Application Problem Based Learning and Discovery Learning Models - Elsa Sinuraya; Nora Susanti; Freddy Tua Musa Panggabean; Eni Rismawati (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
The aim of this research is to determine the improvement and differences in students' scientific literacy abilities taught using the Problem Based Learning and the Discovery Learning model assisted by animated video media on chemical equilibrium material. The sampling technique was carried out using purposive sampling, resulting in class XI IPA 5, totaling 34 students, as experimental class I and XI IPA 6, totaling 36 students, as experimental class II. In learning, the test instrument uses cognitive levels C4 to C6. The results of students' scientific literacy abilities taught using the Problem Based Learning model have increased with an average value from 47.05 to 82.94, as well as the results of students' scientific literacy abilities taught using the Discovery Learning model, namely with an average value of 44.17 to 79.94. Through hypothesis testing using the Independent Sample T-Test with the prerequisites of normality and homogeneity, a Sig (2-Tailed) value of 0.024 was obtained, so it can be concluded that Ha is accepted. The results of this research show that there are differences in the scientific literacy abilities of students taught using the Problem Based Learning and the Discovery Learning model assisted by animated video media on chemical equilibrium material.